A Comparison of Fluorescent Microscopy Methods for the Detection of Chlamydia trachomatis - Lurie, Micaela (Department of Pathology, 2023)
Chlamydia trachomatis (C. trachomatis) is the most common bacterial sexually transmitted pathogen worldwide, especially in low- and middle-income countries, including South Africa. Although frequently asymptomatic, C. trachomatis infections in women cause pronounced genital inflammation. Given that genital inflammation increases women's risk for human immunodeficiency virus (HIV) infection, treating and preventing chlamydia is vital. Thus, there is an urgent need for effective interventions to curb chlamydia infection. Although vaccines are currently in development, none are yet approved for use. New drugs should also be developed and tested given the general rise of antimicrobial resistance. To advance such interventions, expertise in the basic microbiology of C. trachomatis is required. Techniques have indeed advanced over time; however, the standard methods of culture and quantification of C. trachomatis in vitro remain challenging. In South Africa, expertise in C. trachomatis culture and in vitro manipulation is particularly limited. Therefore, I aimed to establish a method to quantify laboratory-adapted stocks of C. trachomatis in in vitro cell culture, to develop research capacity and set the stage for the important future research needed to combat this pathogen. In this study, C. trachomatis was cultured from existing laboratory stocks and used to optimise and compare microscopy-based quantification methods. First, representative C. trachomatis urogenital serovars (E, H) and lymphogranuloma venereum (LGV) serovars (L1 and L2) were propagated in McCoy cells, using an established centrifugation protocol. These stocks were used for all assays comparing three commercially available reagents: (1) Pathfinder's C. trachomatis monoclonal antibody, (2) Invitrogen's C. trachomatis major outer membrane protein (MOMP) antibodies, and (3) Trinity Biotech MicroTrak C. trachomatis culture confirmation kit. In the research setting, fluorescent microscopy techniques are widely used for quantification of C. trachomatis due to their high sensitivity. However, this study showed the Pathfinder C. trachomatis monoclonal antibody kit and Invitrogen's C. trachomatis MOMP Monoclonal Antibody kits had poor sensitivity with high background fluorescent signals. Invitrogen's polyclonal antibody yielded inconsistent results, being either very weakly fluorescent or giving extremely bright signals. Thus, counting bacteria using this polyclonal antibody had limited success and results were not reproducible. MicroTrak's kit, in contrast, allowed for clear visualisation of inclusions and allowed for consistent and successful counting of C. trachomatis bacteria. This study reports inconsistent and/or unreliable results from the kits tested, with two of the three reagents performing poorly. The last, effective kit manufactured by MicroTrak was since discontinued. Thus, molecular methods, particularly qPCRbased methods should be utilised to quantify C. trachomatis in future in vitro cell culture studies.